2016
DOI: 10.1021/acsnano.6b01765
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Surfaces for the Study of Mesenchymal Stem Cell Growth through Adhesion Regulation

Abstract: Out of their niche environment, adult stem cells, such as mesenchymal stem cells (MSCs), spontaneously differentiate. This makes both studying these important regenerative cells and growing large numbers of stem cells for clinical use challenging. Traditional cell culture techniques have fallen short of meeting this challenge, but materials science offers hope. In this study, we have used emerging rules of managing adhesion/cytoskeletal balance to prolong MSC cultures by fabricating controllable nanoscale cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 58 publications
1
81
0
Order By: Relevance
“…There have been attempts to recapitulate the dynamic properties of the ECM using materials that react to external stimuli and ultimately alter the phenotype of the cells. Different types of triggering mechanisms have been utilized including light, either in 2D or 3D (hydrogels) culture systems, inducing irreversible or reversible protein‐material interactions, temperature, and enzymes . However, these systems are typically designed to reveal or hide cell binding sites to/from cells and this still falls short of the dynamic nature of complex niches hMSCs reside in in vivo.…”
mentioning
confidence: 99%
“…There have been attempts to recapitulate the dynamic properties of the ECM using materials that react to external stimuli and ultimately alter the phenotype of the cells. Different types of triggering mechanisms have been utilized including light, either in 2D or 3D (hydrogels) culture systems, inducing irreversible or reversible protein‐material interactions, temperature, and enzymes . However, these systems are typically designed to reveal or hide cell binding sites to/from cells and this still falls short of the dynamic nature of complex niches hMSCs reside in in vivo.…”
mentioning
confidence: 99%
“…A hypothesis we can allude to from the literature is that typically MSCs have more, but smaller, adhesions 38 and, in MSCs, the cell membrane is more teathered to adhesions reflecting that MSCs need to respond to environmental cues 37 . Osteoblasts, on the other hand, in common with other connective tissue cells, are required to withstand the loads mechanical strain places on tisses and so teather the membrane to linker complexes such as the ERM proteins (ezrin, radixin and moesin) 37 ; we have previously reported increased expression of ezrin with onset of MSC osteogenesis 39 . Further, ERM depletion leads to inability to chemically induce osteogenesis 40 .…”
Section: Discussionmentioning
confidence: 90%
“…Designing materials that can control cell–material interactions by external stimuli offers versatile potential to reversibly switch between cell‐adhesive and nonadhesive materials in vivo. Cell–material interactions have been shown to be modulated by various stimuli, such as enzymes, electric fields, magnetic fields, and light . For example, enzymes, such as exonuclease and elastase, were utilized to temporally modulate cell adhesion by dynamically presenting bioactive motifs, such as aptamers and RGD in vitro.…”
Section: Methodsmentioning
confidence: 99%
“…Cell–material interactions have been shown to be modulated by various stimuli, such as enzymes, electric fields, magnetic fields, and light . For example, enzymes, such as exonuclease and elastase, were utilized to temporally modulate cell adhesion by dynamically presenting bioactive motifs, such as aptamers and RGD in vitro. Our own study showed that magnetic field tuned the tether mobility of RGD‐bearing magnetic nanoparticles to modulate cell adhesion in vitro .…”
Section: Methodsmentioning
confidence: 99%